Reviewing the far‐reaching ecological impacts of human‐induced terrigenous sedimentation on shallow marine ecosystems in a northern‐New Zealand embayment - John D. Booth (New Zealand Journal of Marine and Freshwater Research, 2020)
Human settlement in Bay of Islands, New Zealand, beginning ∼1300 AD, wrought immense, conspicuous and enduring change to local shallow‐water marine ecologies, this review addressing those transformations attributable to increased rates of anthropogenically induced, land‐derived sedimentation. Elevated silt inflow, particularly after the late‐1800s, in course led to ∼130% expansion in mangrove ( Avicennia marina ) cover, with concomitant loss of saltmarsh, uppershore coarse‐shell beaches/cheniers, and (probably) intertidal seagrass ( Zostera muelleri ). Sedimentation also led to widespread loss of estuarine shellfish habitat, and, although not necessarily categorically causal, seems, at the same time to have contributed to such degradation among cockle ( Austrovenus stutchburyi ) populations that few individuals attain their potential size. Most changes, many seemingly irreversible, can be described as ecologically catastrophic, with ecosystems altered and destroyed, and uncommon habitats threatened. Sedimentation appears the single‐most important and enduring contributor to ecological degradation in shallow waters of this northern harbour, with time lags between stressor‐onset and realisation of impact (decades to centuries) that only now are becoming clear. Outstanding issues concern establishing the extent of relationship between levels of terrigenous sedimentation and cockles seldom attaining their previous maximum sizes, and origins of the possibly new, widespread phenomenon of living cockles accumulating and dying atop beach surfaces.